2015
DOI: 10.1080/00107514.2015.1026556
|View full text |Cite
|
Sign up to set email alerts
|

The rock–paper–scissors game

Abstract: Rock-Paper-Scissors (RPS), a game of cyclic dominance, is not merely a popular children's game but also a basic model system for studying decision-making in non-cooperative strategic interactions. Aimed at students of physics with no background in game theory, this paper introduces the concepts of Nash equilibrium and evolutionarily stable strategy, and reviews some recent theoretical and empirical efforts on the non-equilibrium properties of the iterated RPS, including collective cycling, conditional response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…First, in contrast to other RPS investigations where individuals played a number of opponents 4 10 , here each participant played only one computerized opponent who acted according to the Nash equilibrium. It has been suggested that in a two-player RPS game, conditional probabilities should only show minor deviation from 33% 26 . Furthermore, the use of a computerized opponent who failed to take advantage of any player’s vulnerability may have also contributed to a fairly conservative test of irrational decision making.…”
Section: Discussionmentioning
confidence: 99%
“…First, in contrast to other RPS investigations where individuals played a number of opponents 4 10 , here each participant played only one computerized opponent who acted according to the Nash equilibrium. It has been suggested that in a two-player RPS game, conditional probabilities should only show minor deviation from 33% 26 . Furthermore, the use of a computerized opponent who failed to take advantage of any player’s vulnerability may have also contributed to a fairly conservative test of irrational decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In this section we focus on another classic game: rock-paperscissors (RPS). This game has been widely studied and used for simulating, e.g., different colonies of bacteria that coexist and interact [11], for studying decision-making in non-cooperative strategic interactions [46] or for representing a food chain in ecosystems [38]. Further studies can be found in [22], [26], [42].…”
Section: Rock-paper-scissorsmentioning
confidence: 99%
“…The empirical attractiveness of the game is derived from the relationships between the items [16], in that there is no one selection that is guaranteed to perform better than another. Due to the unique Nash equilibrium of the game [17], the only strategy that can guarantee the lack of exploitation is the mixed strategy or minimax solution, whereby all three responses are randomly played 33% of the time and without regard for the previous trial [18][19][20][21]. Approximations of the mixed strategy have been reported in pigeons [4], monkeys [22], and professional sports players [23,24].…”
Section: Competitive Decision-makingmentioning
confidence: 99%